2020
DOI: 10.7759/cureus.7822
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxidative Stress and Production of Inflammatory Mediators Matrix Metalloproteinase-9 and Interleukin 6: Systemic Events in Radicular Cysts

Abstract: Background Matrix metalloproteinase-9 (MMP-9) and antioxidants are associated with the pathogenesis of cysts and may initiate and sustain the formation of new capillaries. Objective The objective of this study was to determine the association of oxidative stress and the production of inflammatory mediators MMP-9 and interleukin 6 (IL-6) in systemic events in radicular cyst growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Our results were contradictory in this aspect, to reported by Malik et al . (2020) since the levels of SOD and GPx (57.934 and 102.9 U/mL, respectively) were superior in PPL patients and they reported a significant decrement in patients compared to controls in levels of SOD (0.03 and 0.11 nmol/ml, respectively) and GPx (5.88 and 7.87 nmol/ml, respectively) ( 9 ) Probably by MDA may reduce the activity of glutathione peroxidase in periapical granulomas, as it has been reported by Ayala et al . ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results were contradictory in this aspect, to reported by Malik et al . (2020) since the levels of SOD and GPx (57.934 and 102.9 U/mL, respectively) were superior in PPL patients and they reported a significant decrement in patients compared to controls in levels of SOD (0.03 and 0.11 nmol/ml, respectively) and GPx (5.88 and 7.87 nmol/ml, respectively) ( 9 ) Probably by MDA may reduce the activity of glutathione peroxidase in periapical granulomas, as it has been reported by Ayala et al . ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…When polyunsaturated fatty acids are oxidized by ROS, malondialdehyde (MDA) is produced upon fatty acid decomposition; thus, measurement of MDA has been used as an indicator of LPO ( 21 ). Oxidative stress has an important role in the pathogenesis during PPL formation, for example in a radicular cyst ( 9 ). The levels of lipid peroxidation by MDA analysis have been reported in several investigations as Franco C. (2017), in an experimental study were reported a significant elevation in the levels of MDA in periapical lessons ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations